Dietary pattern among type 2 diabetes in rural area of Mysuru - S., Nishchitha; D., Sunil Kumar; N., Chandan; Gopi, Arun; M. R., Narayan Murthy; Bilimale, Anil S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Type 2 diabetes mellitus is considered one of the most common diseases in the world. It has a complex aetiology that includes both irreversible and reversible risk variables. Diet and its practice, sedentary way of life are the key factors for rapidly rising incidence amongst developing countries. Different methodological approach, to construct their diet patterns and their composition bound to conclusions on healthy patterns for diabetics. The study aimed to assess the dietary pattern among type 2 diabetic patients in rural field practice area of department of community medicine, Suttur, Mysuru. Methods: The study was conducted at rural primary health center, Suttur, Mysore. 384 patients with type 2 diabetes (having for >1 years) aged between 18-70 years formed the study population. Semi-structured questionnaires were used to obtain data about dietary practices and food frequency questionnaire was used to assess food intake. Results: Results revealed 70% were illiterates, 47.9% were between 1-3 years duration of diabetes and 97.4% followed both diet and oral medications. All of them consumed 3 meals a day. Dietary practices incorporated due to diabetic state were: cereals (100%) and fruits (166.6%), meat and poultry (200.6%) weekly. Conclusions: It is one such type of disease which can be prevented at various levels by identifying predictors. Diabetic patients had poor dietary practices and consumed protective foods inadequately. Dietary practices did not change markedly except for reduction in cereals, and fruits.